HUBUNGAN PEMAHAMAN DENGAN PERILAKU IBU RUMAH TANGGA DALAM MENGELOLA LIMBAH RUMAH TANGGA - Pangesti, Dinda Tri; Frinaldi, Aldri (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
Environmental problems are increasingly worrying day by day, this is caused by some pollution by humans, one of which is caused by household waste. Household waste is waste originating from kitchens, bathrooms, laundry, former household industrial waste and human waste. This study used a quantitative method with a type of correlation to see the relationship between the level of understanding and the behavior of managing household waste among housewives. The data collection technique was in the form of distributing questionnaires to housewives in the ABI Lubuk Minturun housing, Koto Tangah District, Padang. The sample of this study was 50 women in the ABI Lubuk Minturun housing, Koto Tangah Padang District. The results of this mini-research conducted by the author show that there is a significant relationship between understanding and the behavior of housewives at ABI Lubuk Minturun Housing District, Koto Tangah Padang in managing household waste with a value of p=0.000. There is a need for socialization and direct education activities for existing households. Keyword : Environmental, Environmental Pollution, Household Waste, Public Health